Mekanisme Pinjaman Kuota Darurat pada Provider Tri dalam Perspektif Hukum Islam - Arif Nur Fauzi; Hendra Karunia Agustine; Eka Eka (AL-MASHALIH (Journal of Islamic Law), 2025)
Emergency Package is a service from Indosat Ooredoo Hutchison (including Tri) for prepaid users in the form of credit or quota paid during the next top-up, either all at once or in installments. This service is not a subscription. Tri users must first activate to purchase emergency quota through the Bima+ application. This service is subject to an administration fee and the quota is only valid for certain applications such as YouTube and Netflix, unlike regular quota. This study aims to determine the mechanism of emergency quota loan, legal status and relevance to Islamic Law. The author uses a qualitative research method by combining field research through interviews and library research from books and journals. Data collection techniques include literature studies, interviews, and documentation. As for the results of research: 1) The results show two problems in the Tri emergency quota mechanism through the Bima+ application. First, there is an additional fee so that the price of the emergency quota is more expensive than the regular quota. Second, the emergency quota is only valid for certain applications without the user's knowledge, creating ambiguity in the contract; 2) A review of Islamic law on the emergency quota loan mechanism on the Tri provider shows that the contract is closer to bai' bitsamanin muajjal (sale and purchase with deferred payment) than qardh (loan), because the customer receives the benefit first and pays later. The additional fee in this service has the potential to contain elements of riba nasi'ah, namely additional costs due to delayed payment, but is still considered valid because it meets the pillars and conditions of the sale and purchase. However, limiting the use of the quota to only certain applications without detailed explanation creates an element of gharar (ambiguity). Therefore, this mechanism is not fully in accordance with sharia principles because it leads to a fasid sale and purchase, namely a transaction that is valid according to the contract but contains defects in its conditions or pillars according to Islamic law.